2010
DOI: 10.1016/j.socscimed.2010.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in childhood dental caries: The convergent roles of stress, bacteria and disadvantage

Abstract: The studies reported here examines stress-related psychobiological processes that might account for the high, disproportionate rates of dental caries, the most common chronic disease of childhood, among children growing up in low socioeconomic status (SES) families. In two 2004 -2006 studies of kindergarten children from varying socioeconomic backgrounds in the San Francisco Bay Area of California (Ns = 94 and 38), we performed detailed dental examinations to count decayed, missing or filled dental surfaces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 56 publications
(58 reference statements)
5
107
2
7
Order By: Relevance
“…Similar result has also been reported in 5-10-year-old children (Rai, Hegde et al 2010). Equivalent results, association between caries and salivary cortisol concentrations have been described in 5-year-old children by Boyce et al (2010). In addition it is reported that 10-14-year-old children with high caries experiences has lower diurnal declines, between morning and afternoon cortisol concentrations in saliva compared to those with low caries experiences (Barbosa, Castelo et al 2012).…”
Section: Stress Response and Dental Cariessupporting
confidence: 77%
“…Similar result has also been reported in 5-10-year-old children (Rai, Hegde et al 2010). Equivalent results, association between caries and salivary cortisol concentrations have been described in 5-year-old children by Boyce et al (2010). In addition it is reported that 10-14-year-old children with high caries experiences has lower diurnal declines, between morning and afternoon cortisol concentrations in saliva compared to those with low caries experiences (Barbosa, Castelo et al 2012).…”
Section: Stress Response and Dental Cariessupporting
confidence: 77%
“…Dental caries is a chronic infectious disease resulting from the penetration of oral bacteria into the enamel and dentin; microorganisms subsequently trigger inflammatory responses in the dental pulp [63]. Childhood dental caries constitutes the single most common chronic disease, affecting as many as 60-90% of children worldwide between the ages of 2 and 11 years [64]. Many parents, particularly those from low socioeconomic status, are less attentive to the dental hygiene of their children; this is evidenced by the fact that, on medical follow-up two years later, children participants were still found with dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations include the adoption of unhealthy dietary habits and lifestyles by this segment of the population and exposure to a number of factors that undermine health, or a combination of these factors. However, the socioeconomic factors associated with prevalence of dental caries do not fully explain the reason for the caries phenomenon 3 , which may be influenced by social, genetic, biological and cultural factors 4 . Tooth decay has been described as a "sentinel disease" for other pediatric conditions 1 , with dental care being the most commonly unmet need 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of programs directed at reducing cost or access barriers show that these obstacles are merely part of this multidimensional dental health problem 3,11 .…”
Section: Introductionmentioning
confidence: 99%